1997
DOI: 10.1007/s004410050815
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-induced uterine neuronal degeneration in the rat

Abstract: We studied the location, distribution, and density of uterine nerve bundles in virgin, full-term pregnant, and early postpartum female rats. In the virgin, a low-magnification analysis of uterine whole-mounts stained for acetylcholinesterase revealed fibers both in close association with blood vessels and coursing freely within muscle or connective tissue in the mesometrium and the uterine body. Higher magnification analysis of sections treated immunohistochemically with antibodies to the ubiquitous neuronal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 34 publications
6
56
0
1
Order By: Relevance
“…Several studies have led to the concept that AChE staining is not a reliable marker for cholinergic nerves (Garfield 1986;Papka et al 1999), because AChE histochemistry has also been shown to stain sympathetic (Haase et al 1997) and primary afferent sensory nerve fibers (Papka et al 1981). In addition, it has been demonstrated that, in several target organs, postganglionic sympathetic and parasympathetic nerve fibers run closely juxtaposed within a common Schwann cell sheath (Ehinger and Falk 1966;Ehinger et al 1970;Elbadawi 1984;Levi 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have led to the concept that AChE staining is not a reliable marker for cholinergic nerves (Garfield 1986;Papka et al 1999), because AChE histochemistry has also been shown to stain sympathetic (Haase et al 1997) and primary afferent sensory nerve fibers (Papka et al 1981). In addition, it has been demonstrated that, in several target organs, postganglionic sympathetic and parasympathetic nerve fibers run closely juxtaposed within a common Schwann cell sheath (Ehinger and Falk 1966;Ehinger et al 1970;Elbadawi 1984;Levi 1990).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have known for some time that the uterus becomes essentially denervated during gestation [4] and as a result, it is unlikely that any coordinated nervous regulation of the myometrium is centrally orchestrated [5] . As a result, views of the origin of onset of labor turned early on to examine endocrine and paracrine mechanism of myometrial regulation.…”
Section: The Onset Of Labormentioning
confidence: 99%
“…For example, Papka et al (1985) were unable to analyze whole mounts extensively because of their thickness and the many different focal planes that needed to be examined and photographed. Haase et al (1997) examined acetylcholinesterase (AChE)-stained uterine whole-mount preparations floating in glycerin with a dissecting microscope and needed careful manipulation of light sources for assessment. Nevertheless, these authors were only able to publish low-magnification diagrams of AChE staining, which contained little detail about the actual trajectories of cholinesterase-positive nerve bundles and axons.…”
mentioning
confidence: 99%